Faktor–Faktor Yang Mempengaruhi Stunting Pada Balita Di Desa Karay dan Desa Angar Kabupaten Seram Bagian Timur - Tamar, Tamar; Moniharapon, Erynola; Sipahelut, Sophia G; Mailoa, Meitycorfrida (Jurnal Agrosilvopasture-Tech, 2023)
Karay Village and Angar Village are one of sub-districts which are registered in East Seram Regency as villages with children registered as stunting toddlers. The type of research used was Spearman's correlation with a total of 60 samples of toddlers in Karay Village and Angar Village. Research methods using surveys and interviews using a questionnaire. The results of this study used sperman rho palm fiber using univariate and bivariate analysis. This research is that there is a relationship between maternal education, consumption of various foods, toilet facilities, drinking water facilities, and livable homes with the incidence of stunting in toddlers aged 0-5 years in Karay and Angar District. Based on the results of the study, it showed that there was a relationship between Mother's Education (P < 0.05), Consumption of Various Foods (P < 0.05), Latrine Facilities (P < 0.05), Drinking Water Facilities (P < 0.05), and Livable Houses (P < 0.05), on the other hand, there was no relationship between the age of marriage (P > 0.05), the number of children (P > 0.05) and the mother's source of income (P > 0.05) with the incidence of stunting in children under five in Karay Village and Angar Village.